Pregnancy and HIV disease progression: a systematic review and meta‐analysis. Issue 2 (31st October 2014) - Calvert, Clara; Ronsmans, Carine
Abstract Objective To assess whether pregnancy accelerates HIV disease progression. Methods Studies comparing progression to HIV‐related illness, low CD4 count, AIDS‐defining illness, HIV‐related death, or any death in HIV‐infected pregnant and non‐pregnant women were included. Relative risks (RR) for each outcome were combined using random effects meta‐analysis and were stratified by antiretroviral therapy (ART) availability. Results 15 studies met the inclusion criteria. Pregnancy was not associated with progression to HIV‐related illness [summary RR: 1.32, 95% confidence interval (CI): 0.66–2.61], AIDS‐defining illness (summary RR: 0.97, 95%CI: 0.74–1.25) or mortality (summary RR: 0.97, 95%CI: 0.62–1.53), but there was an association with low CD4 counts (summary RR: 1.41, 95%CI: 0.99–2.02) and HIV‐related death (summary RR: 1.65, 95%CI: 1.06–2.57). In settings where ART was available, there was no evidence that pregnancy accelerated progress to HIV/AIDS‐defining illnesses, death and drop in CD4 count. In settings without ART availability, effect estimates were consistent with pregnancy increasing the risk of progression to HIV/AIDS‐defining illnesses and HIV‐related or all‐cause mortality, but there were too few studies to draw meaningful conclusions. Conclusions In the absence of ART, pregnancy is associated with small but appreciable increases in the risk of several negative HIV outcomes, but the evidence is too weak to draw firm conclusions. When ART is available, the effects of pregnancy on HIV disease progression are attenuated and there is little reason to discourage healthy HIV‐infected women who desire to become pregnant from doing so.